Career choices of migrant artists between Amsterdam and Antwerp. The Van Nieulandt brothers - Jan Sluijter, Eric (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2015)
This essay examines the career choices of the brothers Guilliam ii and Adriaen ii van Nieulandt. Both were born in Antwerp but moved with their parents to Amsterdam at a young age. Guilliam returned to Antwerp to make his career, while Adriaen became embedded in Amsterdam’s artistic community. All members of their family – in Antwerp, Amsterdam and Rome – remained in close contact with each other, though changes in the religious and political culture left their mark on their professional decisions. Their choices did not yield artistic innovations but conservative styles and subjects based on shared Netherlandish traditions with a strong international flavour.